Oxysterols and lipidomic profile of myocardium of rats supplemented with pomegranate seed oil and/or bitter melon aqueous extract – Cardio-oncological animal model research. (March 2021) - Białek, Agnieszka; Białek, Małgorzata; Lepionka, Tomasz; Pachniewicz, Paulina; Czauderna, Marian
Highlights: PSO and BME in ongoing breast cancer process did not exert cardio-protective influence. PSO and BME did not inhibit oxysterols formation in hearts in cancerous process. CLA are incorporated into cardiac tissue to a lesser extent in cancerous process. PSO slightly diminished MDA amount in cardiac tissue of DMBA-treated rats. PSO slightly inhibit squalene to cholesterol conversion in DMBA-treated rats. Abstract: A close link between cardiovascular diseases and cancer results from sharing the same modifiable risk factors (e.g. nutritional) and cardiotoxicity of anti-cancerous therapies. It justifies cardio-oncological preliminary studies on dietary factors, especially on those of possible anti-carcinogenic or cardioprotective properties. The main purpose was to evaluate the effect of pomegranate seed oil (PSO) and/or bitter melon extract (BME) supplementation of the diet of female rats suffering from mammary tumors on lipidomic profile (expressed as fatty acids, conjugated fatty acids (CFA), malondialdehyde (MDA), cholesterol and oxysterols content) of cardiac tissue. Total lipidomic profile and intensity of lipid peroxidation in hearts of DMBA-treated Sprague-Dawley rats and their healthy equivalents, both obtaining diet supplementation, were evaluated with different chromatographic techniques coupled with appropriate detection systems (GC–MS, GC-TOFMS, Ag+-HPLC-DAD, UF-HPLC-DAD). Dietary modifications neither diminished breast cancer incidence nor exerted explicit cardio-protective influence, however, they diminished cholesterol content, i.a. because of inhibition of the endogenous conversion of squalene to cholesterol in cardiac tissue. CFA were incorporated into cardiac tissue to a lesser extent in the cancerous process. PSO and BME anti-oxidant properties in pathological condition were only slightly reflected in MDA levels but not in oxysterols formation. Obtained results indicate considerable changes in dietary supplements' biological activity in pathological conditions and the need for clear distinction of drugs and dietary supplements, which is of utmost importance, especially for cancer survivors.